(3GdTNUjI GdbGfhfjI GdOhdjI aj GdESdGe (B:s (3OQGSI ebGQfI aj GdbGfhf GdOhdj GdYGe (B= International legal personality in islam : a comparative study in public international law /s - (3GdaJdGhj, Sgjd MSjf,s 1941- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3jJfGhd cJGH (B((3GdTNUjI GdbGfhfjI GdOhdjI aj GdESdGe (B: (3OQGSI ebGQfI aj GdbGfhf GdOhdj GdYGe(B) (3hGdPj bGe HJCdjag Sgjd MSjf GdaJdGhj aj MhGdj (B(368) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdESdGe hGdbGfhf GdOhdj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3GdTNUjI GdbGfhfjI ddOhdI aj GdESdGe, GdaUd GdChd (B: (3GdOhdI GdESdGejI YfO GHf NdOhf, GdaUd GdKGfj (B: (3OhdI GdeOjfI, GdaUd GdKGdK (B: (3GdOhdI aj YgO GdNdGa GdESdGejI, GdaUd GdQGHY (B: (3Mbhb GdOhd hhGLHGJgG aj GdESdGe, GdHGH GdKGfj (B: (3CTNGU bGfhfjI OhdjI ESdGejI ef ZjQ GdOhd, GdaUd GdChd (B: (3GdTNUjI GdbGfhfjI GdOhdjI aj GdESdGe, GdaUd GdKGfj (B: (3GdTNUjI GdbGfhfjI GdOhdjI ddcjGfGJ GdOjfjI ZjQ GdESdGejI, GdaUd GdKGdK (B: (3GdTNUjI GdbGfhfjI GdOhdjI ddaQO (B((3GdehXa GdOhdj aj GdESdGe(B)(3, GdaUd GdQGHY (B: (3GdTNUjI GdbGfhfjI GdOhdjI GdESdGejI ddCMdGa GdYScQjI, Ke jfJgj HbGFeI GdeUGOQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B349-365.s
Keywords: (3GdESdGe hGdbGfhf GdOhdjs; (3GdESdGe hGdbGfhfs